PENERAPAN PEMBELAJARAN DARING TERHADAP MOTIVASI BELAJAR MAHASISWA MATA KULIAH MANAJEMEN PERBANKAN DI MASA PANDEMI COVID-19 TAHUN AKADEMIK 2020/2021 - Sunarti Djoko (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2021)
ABSTRACT This study aims to determine the impact of the application of online learning on student learning motivation in banking management courses during the covid-19 pandemic. This type of research uses a descriptive qualitative approach..The data collection procedure was carried out by means of observation, interviews and documentation. Data analysis in this study was processed through three stages, namely data reduction, data presentation and conclusion drawing. The research shows that first; student learning motivation is not the same as when participating in learning that is carried out directly in the classroom. Students are more enthusiastic about participating in the learning that the lecturer conveys in the classroom compared to online learning carried out during the covid-19 pandemic through the google classroom and whatsapp applications. Second, the inhibiting factors are: students have difficulty understanding the subject matter delivered via video because they run out of quota when participating in learning delivered through the application.difficulty getting a stable network or signal when participating in learning, so that the learning obtained is less than optimal, while the supporting factors are: making it easier for lecturers to deliver material via smartphones, delivering material to be more interesting and not monotonous, making it easy for students to access other learning resources needed. Keywords: Learning motivation, online learning during the covid-19 pandemic.